Continuous Flow Reactor for the Controlled Synthesis and Inline Photocatalysis of Antibacterial Ag2S Nanoparticles. (28th July 2020) - Prakash, Bhanu; Katoch, Vibhav; Shah, Asmita; Sharma, Manju; Devi, M. Manolata; Panda, Jiban J; Sharma, Jadab; Ganguli, Ashok Kumar
Abstract: The present study is focused on the integration of microreactors to synthesize visible light active nanophotocatalysts for inline photocatalytic degradation of organic dye and antibacterial activity. A wire‐assisted and a rapid laser micromachining technique has been employed for the fabrication of polydimethylsiloxane (PDMS) and poly(methyl methacrylate) (PMMA)‐based microreactors, respectively. By varying the design and chemical reagents involved, different sizes of visible light active Ag2 S nanoparticles were prepared via a continuous microfluidics approach using fabricated microreactors. When polyvinylpyrrolidone (PVP) was utilized as the capping agent during the reaction, smaller particles of the size of 15 nm were observed. The photocatalytic performance of these nanoparticles has been evaluated inline by employing the single‐inlet planar microreactor as a function of flow rate and channel length. The photocatalyst durability test and a comparative photocatalytic efficiency study between the microreactor and the conventional beaker reactor have also been carried out. Under visible light, these nanoparticles exhibit a remarkable enhancement of 94.5% in the inline microreactor‐based photocatalytic degradation of methylene blue dye. The slower the flow rate and longer the channel length, gradual enhancement in the performance has been observed. Also, these nanoparticles express an antibacterial effect with very high efficacy even at very low (2 mg mL −1 ) concentration toward the inhibition of Escherichia Coli . Abstract : Synthesis of antibacterial Ag2S nanoparticles by a facile PDMS microreactor using wire‐assisted fabrication and in‐channel photocatalytic degradation of methylene blue.